Cutaneous Adverse Drug Reactions in Dogs Treated with Antiepileptic Drugs - Koch, Tina; Mueller, Ralf S.; Dobenecker, Britta; Fischer, Andrea (Frontiers in Veterinary Science, 2016)
Epilepsy is one of the most common neurologic disorders in dogs and life-long treatment with antiepileptic drugs (AED) is frequently required. Adverse events of antiepileptic drugs targeting the skin are only rarely reported in veterinary medicine and the true incidence and spectrum of cutaneous reactions in epileptic dogs remains unknown. In this study we hypothesized that cutaneous reactions commonly occur in epileptic dogs and are related to AED treatment. A retrospective case review of 185 dogs treated for epilepsy identified 20.0% with simultaneous appearance of dermatologic signs. In a subsequent prospective case investigation (n=137) we identified newly appearing or distinct worsening of skin lesions following initiation of antiepileptic drug therapy in 10.9% of dogs treated for epilepsy (95% CI 6.8- 17.7%). Cutaneous lesions were classified as probably drug-induced in 40.0% of these cases. Patch-testing and intradermal testing was further investigated as potential diagnostic methods to confirm antiepileptic drug hypersensitivity. They were of high specificity but sensitivity and positive predictive value appeared inappropriate to recommend their routine use in clinical practice.